THE ROLE OF BALILIF PROPER AND FORMAL SUMMONS IN PRIVATE SETLEMENT AT DISTRICT COURT OF BANDUNG AND BALE BANDUNG - Afriana, Anita (Tadulako University, 2018)
One of the officers who engage actively as an executive in court is a bailiff. All duties and obligations undertaken by the bailiff are conducted officially and properly in line with the law. Bailiffs execute their mandate and functions in enforcing the law, as they are the forefront of the court. This article presents a part of a research results conducted with normative juridical research method with a descriptive analytical specification. The research prioritizes secondary data complemented by primary data. The research examines issues on official and proper practices of bailiff summons at District Court of Bandung and Bale Bandung as well as legal consequences if the summon is improper in relation to legal certainty. The research concludes that in practice, the summons have been conducted properly based on the law as provided in Article 122 HIR. However, in some cases, due to certain factors, there are summons carried out properly, but informally. Improper and informal summons conducted due to negligence of the bailiffs may cause harm or loss to the litigants as it can complicate the case settlement, hence, the process becomes longer that leads to more legal cost. Further, this practice disregards the primary purpose of the law itself: legal certainty.